LANGUAGE DEATH IN INDONESIA: A SOCIOCULTURAL PANDEMIC - James T. Collins (Linguistik Indonesia, 2022)
The number of languages in Indonesia exceeds seven hundred, but more than 70% of these languages are spoken in eastern Indonesia, where many speakers of heritage languages are shifting their allegiance to local dialects of Malay or to Indonesian. This essay focuses on the languages of Buru and Seram and the nearby islands of Maluku Province. Because parts of this region formed the earliest Dutch colony in Indonesia, historical documentation allows us to explore language use and language vitality since the sixteenth century. The essay is divided into two parts. In Part 1, materials available from the colonial period are examined and summarized. They reveal that as early as the nineteenth century many languages of this region, especially on the island of Ambon, were already extinct because villagers had become monolingual speakers of Ambonese Malay. In Part 2, reports and academic studies written after 1945 are reviewed. In this post-colonial era, language loss has continued, perhaps even accelerated; some socioeconomic factors are suggested. In the conclusion, the profiles of eight of the Maluku languages estimated in 1983 to have fewer than fifty speakers are compared to the most recent reports of language use and language shift. All eight of these languages are now extinct or on the verge of extinction. This essay, sketching language shift and language death, has implications for all the languages of Indonesia. How can local communities working with government officials and linguists act decisively to maintain and revitalize their ancestral languages?Â Â